2009
DOI: 10.1016/s1470-2045(09)70063-4
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer and aneusomy 17: implications for carcinogenesis and therapeutic response

Abstract: Abnormalities of chromosome 17, recognised over two decades ago to be important in tumorigenesis, often occur in breast cancer. Changes of specific loci on chromosome 17 including ERBB2 amplification, P53 loss, BRCA1 loss, and TOP2A amplification or deletion are known to have important roles in breast-cancer pathophysiology. Numerical aberrations of chromosome 17 are linked to breast-cancer initiation and progression, and possibly to treatment response. However, the clinical importance of chromosome 17 anomali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
86
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(93 citation statements)
references
References 71 publications
4
86
0
3
Order By: Relevance
“…However, the most accurate method of assessing HER2 status is yet to be determined, and interpretation guidelines 3 as given by American Society of Clinical Oncology/College of American Pathologists may give conflicting results, depending Although this appears rather straightforward, abnormalities of chromosome 17 in breast cancer are frequent and may include whole chromosome copy number gains (polysomy 17) or losses (monosomy 17), focal copy number gains and losses, and other structural rearrangements. 10 These abnormalities of chromosome 17 can lead to discrepant interpretations of FISH data, depending on which criterion is used.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the most accurate method of assessing HER2 status is yet to be determined, and interpretation guidelines 3 as given by American Society of Clinical Oncology/College of American Pathologists may give conflicting results, depending Although this appears rather straightforward, abnormalities of chromosome 17 in breast cancer are frequent and may include whole chromosome copy number gains (polysomy 17) or losses (monosomy 17), focal copy number gains and losses, and other structural rearrangements. 10 These abnormalities of chromosome 17 can lead to discrepant interpretations of FISH data, depending on which criterion is used.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13] In a recently published series by Vanden Bempt et al, >40% of breast carcinomas were found to harbor increased CEP17 copy number.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in breast cancer, monosomy of centromere 17 (Cep17), unlike polysomy, has been shown to be a rare event. 12 Few studies are available on the correlation of chromosome 17 abnormalities with prognostic and predictive parameters in invasive breast cancer.…”
mentioning
confidence: 99%
“…El caso 28 (carcinoma de mama) es interesante porque presentó monosomía del cromosoma 17, considerada una alteración cromosómica común durante el desarrollo de esta neoplasia (17,34). Es bien conocido que los genes BRCA1, HER2/ neu y el TP53 están asociados con la génesis del cáncer de mama (1,7,9,32).…”
Section: Discussionunclassified